2020
DOI: 10.1055/s-0040-1702920
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Inhibition in Acute Coronary Syndrome and Percutaneous Coronary Intervention: Insights from the Past and Present

Abstract: Platelet activation and aggregation have a pivotal role in arterial thrombosis and in the pathogenesis of both acute coronary syndromes (ACS) and in the thrombotic complications that occur in patients undergoing percutaneous coronary intervention (PCI). The past 30 years has seen the progress from early trials of clopidogrel and glycoprotein IIb/IIIa inhibitors to the application of more potent P2Y12 inhibitors prasugrel and ticagrelor. Early enthusiasm for newer and more potent antiplatelet agents, which coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 107 publications
0
15
0
Order By: Relevance
“…32 Up to a third of ACS patients demonstrate inadequate platelet inhibition in response to clopidogrel. 33 This is explained in part by polymorphisms in the gene encoding the hepatic enzyme CYP2C19, which transforms clopidogrel to its active metabolite, that can result in 5-12% variation in platelet inhibition. 34 There is ethnic variation in the prevalence of the loss-of-function CYP2C19 618G>A*2 allele, affecting some 30% of Caucasians and 50% of East Asians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…32 Up to a third of ACS patients demonstrate inadequate platelet inhibition in response to clopidogrel. 33 This is explained in part by polymorphisms in the gene encoding the hepatic enzyme CYP2C19, which transforms clopidogrel to its active metabolite, that can result in 5-12% variation in platelet inhibition. 34 There is ethnic variation in the prevalence of the loss-of-function CYP2C19 618G>A*2 allele, affecting some 30% of Caucasians and 50% of East Asians.…”
Section: Discussionmentioning
confidence: 99%
“…34 There is ethnic variation in the prevalence of the loss-of-function CYP2C19 618G>A*2 allele, affecting some 30% of Caucasians and 50% of East Asians. 33 Homozygotes for the CYP2C19*2 and less common CYP2C19*3 LoF alleles are poor metabolizers, and heterozygotes are intermediate metabolizers of clopidogrel, with high-on clopidogrel platelet reactivity and increased risk of adverse cardiovascular events, including AMI and stent thrombosis. [35][36][37] The association of CYP2C19 genotype with increased cardiovascular risk appears greatest in those undergoing PCI, and the risk is greater in Asians than in whites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute coronary syndrome (ACS) is the leading cause of morbidity and mortality in developed countries [ 1 ]. The combination of treatment with a platelet P2Y12 receptor inhibitor, such as clopidogrel, prasugrel, or ticagrelor with acetylsalicylic acid (dual antiplatelet therapy, DAPT), has been shown to prevent coronary peri-procedural thrombotic complications and recurrent ischemic events [ 2 , 3 ]. Randomized controlled trials have shown a reduced reoccurrence of ACS in patients treated with a DAPT comprising prasugrel or ticagrelor compared to clopidogrel [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…From the other perspective, up to 36% of patients with AF have concomitant coronary artery disease (CAD) amongst whom 45% have prior MI [ 3 , 4 ]. Treatment of ACS, with or without percutaneous coronary intervention (PCI), requires the administration of dual antiplatelet therapy (DAPT) to prevent recurrent MI and stent thrombosis (ST) [ 5 , 6 ]. In most patients with AF, oral anticoagulation (OAC) is indicated for the prevention of stroke and systemic embolism [ 7 ].…”
Section: Introductionmentioning
confidence: 99%